Influence of W doping on the structure, magnetism and exchange bias in Ni47Mn40Sn13−xWx Heusler alloys. (1st June 2022) - Norouzi-Inallu, M; Kameli, P; Ghotbi Varzaneh, A; Abdolhosseini Sarsari, I; Abbasi Eskandari, M; Orue, I; Rodríguez-Crespo, B; Chernenko, V
Abstract: The influence of the W-doping on the martensitic transformation, magnetic properties and exchange bias (EB) effect in the Ni47 Mn40 Sn13− x W x ( x = 0, 0.5, 1, 1.25 at.%) magnetic shape memory alloys has been investigated. It is found that the W-doping causes a simultaneous reduction of both the ferromagnetic (FM) exchange coupling and enhancement of the magnetic anisotropy, leading to a decrease of the magnetic moment of the low-temperature phase and to a higher attainable EB. The magnetic memory measurements reveal the presence of a glassy magnetic ground state, which can significantly impact the reduction of magnetization and enhancement of EB in the studied bulk alloys. It is argued that the glassy magnetic ground state originates from the partial magnetic disorder resulting from the correlation between the antiferromagnetic and FM states. The results demonstrate that the doping by W instead of Sn is an efficient tool to tailor the EB effect in the Ni–Mn–Sn-based Heusler alloys, whereby they are promising for spintronic applications.